2012
DOI: 10.4142/jvs.2012.13.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a selenium-independent glutathione peroxidase (HC29) from adultHaemonchus contortus

Abstract: The complete coding sequence of Haemonchus (H.) contortus HC29 cDNA was generated by rapid amplification of cDNA ends in combination with PCR using primers targeting the 5'- and 3'-ends of the partial mRNA sequence. The cloned HC29 cDNA was shown to be 1,113 bp in size with an open reading frame of 507 bp, encoding a protein of 168 amino acid with a calculated molecular mass of 18.9 kDa. Amino acid sequence analysis revealed that the cloned HC29 cDNA contained the conserved catalytic triad and dimer interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The K m assay of rPsGPx demonstrated that it could catalyze H 2 O 2 in the presence of GSH, which further proved that rPsGPx was a GPx of the thioredoxin-like family. 19 As compared with other reported GPxs from different organisms, rPsGPx exhibits some distinct enzymatic properties. For example, rPsGPx manifested the highest activity at 30 C and retained at least 40% activity even at 0 C (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The K m assay of rPsGPx demonstrated that it could catalyze H 2 O 2 in the presence of GSH, which further proved that rPsGPx was a GPx of the thioredoxin-like family. 19 As compared with other reported GPxs from different organisms, rPsGPx exhibits some distinct enzymatic properties. For example, rPsGPx manifested the highest activity at 30 C and retained at least 40% activity even at 0 C (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…18 In this study, rPsGPx contained three active site residues (Cys 72 , Gln 103 , and Trp 154 ), and the amino acid residues were conserved in all other members and were vital for active-site structure. 17,19,20 Meanwhile, the GPx from adult Haemonchus contortus possessed active site residues Cys 38 , Gln 73 , and Trp 127 , 19 whereas the GPx from halotolerant Chlamydomonas sp. W80 contained amino acid residues Cys 37 , Gln 71 , and Trp 125 .…”
Section: Discussionmentioning
confidence: 99%
“…F. gigantica -derived ESPs, identified in the present study (rFgTPx) and in previous studies (rFg14-3-3e [ 20 ] and rFgRab10 [ 21 ]), have induced Th1 (IFN-γ, IL-2) and Th2 (IL-4, IL-10, TGF-β) cytokines, except IL-4 and IFN-γ, whose levels were low in response to rFg14-3-3e. Cytokines are produced by a variety of immune cells and play various roles in protecting the host and maintaining tissue homeostasis [ 28 , 29 ]. In an earlier study on F. gigantica infection in buffaloes, we observed that a mixed Th1/Th2 immune response is dominant from 28 to 70 dpi, to promote F. gigantica survival while limiting host tissue damage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major functional differences between Se-GPxs and NS-GPxs is that Se-GPxs catalyse the reduction of both organic and inorganic peroxides like H 2 O 2 , whereas NS-GPxs react preferentially with organic peroxides (Tang et al 1995;Sun et al 2012). One of the major functional differences between Se-GPxs and NS-GPxs is that Se-GPxs catalyse the reduction of both organic and inorganic peroxides like H 2 O 2 , whereas NS-GPxs react preferentially with organic peroxides (Tang et al 1995;Sun et al 2012).…”
Section: Discussionmentioning
confidence: 99%